Quantifying Greenland freshwater flux underestimates in climate models - Christopher M. Little; Christopher G. Piecuch; Ayan H. Chaudhuri (Geophysical Research Letters)
Abstract Key processes regulating the mass balance of the Greenland Ice Sheet (GIS) are not represented in current‐generation climate models. Here using output from 19 different climate models forced with a high‐end business‐as‐usual emissions pathway, we compare modeled freshwater fluxes (FWF) to a parameterization based on midtropospheric temperature. By the mid 21st century, parameterized GIS FWF is 478 ± 215 km3 yr−1 larger than modeled—over 3 times the 1992–2011 rate of GIS mass loss. By the late 21st century, ensemble mean parameterized GIS FWF anomalies are comparable to FWF anomalies over the northern North Atlantic Ocean, equivalent to approximately 11 cm of global mean sea level rise. The magnitude and spread of these underestimates underscores the need for assessments of the coupled response of the ocean to increased FWF that recognize: (1) the widely varying freshwater budgets of each model and (2) uncertainty in the relationship between GIS FWF and atmospheric temperature.